2006
DOI: 10.1158/1055-9965.epi-05-0772
|View full text |Cite
|
Sign up to set email alerts
|

Heme and Chlorophyll Intake and Risk of Colorectal Cancer in the Netherlands Cohort Study

Abstract: Background: The evidence for red meat as a determinant of colorectal cancer remains equivocal, which might be explained by differences in heme content. Heme is the prooxidant, iron-containing porphyrin pigment of meat and its content depends on the type of meat. Chlorophyll from green vegetables might modify this association. Methods: The Netherlands Cohort Study was initiated in 1986 when a self-administered questionnaire on risk factors for cancer was completed by 120,852 subjects ages 55 to 69 years. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
153
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 34 publications
5
153
1
4
Order By: Relevance
“…Our results for haem iron may vary from earlier research (Lee et al, 2004; that calculated haem iron as standard proportions of total iron from meat (Monsen and Balintfy, 1982;Balder et al, 2006), as we estimated haem iron based on measured values from meat samples. The pattern of risk that we observed for haem iron was similar to that for red meat.…”
Section: Discussioncontrasting
confidence: 95%
“…Our results for haem iron may vary from earlier research (Lee et al, 2004; that calculated haem iron as standard proportions of total iron from meat (Monsen and Balintfy, 1982;Balder et al, 2006), as we estimated haem iron based on measured values from meat samples. The pattern of risk that we observed for haem iron was similar to that for red meat.…”
Section: Discussioncontrasting
confidence: 95%
“…Heme iron, which has greater bioavailability compared to non-heme iron, has been shown experimentally to have cytotoxic and hyperproliferative effects in the rat colon (Sesink et al, 1999). To date, three cohort studies have reported on the association of heme iron intake and risk of colon or colorectal cancer (Lee et al, 2004;Larsson et al, 2005;Balder et al, 2006), and suggest a possible positive association of intake with risk, which may be enhanced in consumers of alcohol. However, there are inconsistencies in the association found in these studies by subsite (Lee et al, 2004;Larsson et al, 2005) and by sex (Balder et al, 2006), as well as with regard to the role of effect modification by alcohol consumption.…”
mentioning
confidence: 99%
“…Total intake of meat iron was calculated from the reported intake of 22 meat items and 2 mixed dishes containing meat. Heme iron intake was computed by two different methods using different proportions for heme iron from different types of meat: 69% for beef; 39% for pork, ham, bacon, pork-based luncheon meats, and veal; 26% for chicken and fish; and 21% for liver (20); and, alternatively, using 40% as the average proportion of heme iron in all meats (21). Results were similar for both methods, and we present data using the first approach.…”
Section: Methodsmentioning
confidence: 94%